2014
DOI: 10.1002/aic.14674
|View full text |Cite
|
Sign up to set email alerts
|

Surface tension, adsorption, and wetting behaviors of natural surfactants on a PTFE surface

Abstract: in Wiley Online Library (wileyonlinelibrary.com) The adsorption kinetics and wetting behaviors of three plant-based natural surfactants (Reetha, Shikakai, and Acacia) on the polytetrafluoroethylene (PTFE) surface are reported in this study. Adsorption studies of these surfactants on PTFE surface show the equilibrium adsorption time is approximately 15 min, and Langmuir-type isotherm fits well for all three surfactants. The contact angle measurements show that the value achieved by Reetha and Acacia solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…The variations of the contact angle values with the increasing concentration of 18C and 18S are presented in Figure 2 for PTFE and PMMA surfaces. Figure 2a clearly depicts that the dependency of contact angle with the logarithm of concentrations on the PTFE surface are different from other researchers' conclusions[12,18,19,31] : for 18C and 18S, the contact angle keep almost a constant value in a wide range of surfactant concentration even more than CMC of individual surfactant solution.Above 1×10 -4 mol/L, the contact angles of both 18C and 18S show rapid downward trend and the values of 18C are significantly lower than that of 18S. However, for the conventional surfactants, there is a decrease in contact angle with the increase in surfactant concentration until CMC of surfactant solution and above that it is almost constant.…”
mentioning
confidence: 52%
“…The variations of the contact angle values with the increasing concentration of 18C and 18S are presented in Figure 2 for PTFE and PMMA surfaces. Figure 2a clearly depicts that the dependency of contact angle with the logarithm of concentrations on the PTFE surface are different from other researchers' conclusions[12,18,19,31] : for 18C and 18S, the contact angle keep almost a constant value in a wide range of surfactant concentration even more than CMC of individual surfactant solution.Above 1×10 -4 mol/L, the contact angles of both 18C and 18S show rapid downward trend and the values of 18C are significantly lower than that of 18S. However, for the conventional surfactants, there is a decrease in contact angle with the increase in surfactant concentration until CMC of surfactant solution and above that it is almost constant.…”
mentioning
confidence: 52%
“…To date, the wetting behavior of surfactant solutions on abiotic solid surfaces has been extensively researched [9,10,11,12,13]. In comparison to abiotic solid surfaces, the wetting behavior of plant surfaces is more complicated, as seen in wheat [14], ginkgo leaves [15], and rice [16].…”
Section: Introductionmentioning
confidence: 99%
“…trifiliatus are 102.6 • and 73 • , respectively. Paria et al [25] found for Sp. mukorossi 109.88 • as the minimum contact angle.…”
Section: Resultsmentioning
confidence: 90%